Multi-channel multi-radio ad hoc network - Ng, Tiffany Sook Mun. (2012)
Mobile Ad hoc networks are deployed in 1990’s and have been widely researched for many years since then. It consists of two or more devices communicating wirelessly. These devices can communicate with other nodes that are within their radio range or one that is outside their radio range. Nodes should deploy an intermediate node to be the router to route the packet from the source towards the destination. Mobile Ad hoc networks do not have gateway, every node is able to be the gateway.